Efektivitas Supervisi Manajerial dan Akademik dalam Meningkatkan Mutu Pembelajaran Guru di MTsN 3 Kota Kediri - Adzhar, Moh Hanif; Aryadana, Addin (Universitas Pakuan, 2025)
This research aims to explore and examine the effectiveness of managerial and academic supervision in educational institutions as an effort to improve the quality of teacher learning. The implementation of supervision aims to ensure that MTsN 3 Kota Kediri can at least maintain and improve the quality of teacher learning through optimizing comprehensive supervision evaluation. This research uses a case study method, where data is obtained through observation, interviews and documentation. The results showed that managerial and academic supervision at MTsN 3 Kota Kediri plays an important role in improving the quality of teacher learning. Managerial supervision ensures the effectiveness of madrasah governance, including planning, resource management and evaluation of education policies, while academic supervision focuses on improving teachers' pedagogical competence through observation, guidance and training. Through the systematic and sustainable implementation of supervision, teachers can develop more innovative learning strategies, improve their professionalism and create a more effective learning environment for students.